Relationship between thyroid hormone and sex hormone levels and non-suicidal self-injury in male adolescents with depression - Ma, Jiahui; Zhao, Mingming; Niu, Gengyun; Wang, Zhifei; Jiang, Shan; Liu, Zengxun (Frontiers in Psychiatry, 2022)
Objective Nonsuicidal self-injury (NSSI) is the intentional and repeated direct injury to one's bodily tissues or organs without the intent to die, which is not socially sanctioned and does not result in death. This study will be the first to explore the relationship between NSSI behavior and thyroid hormone and sex hormone levels in male adolescents with depression. Methods Among the inpatients in the children's ward of Shandong Mental Health Center, eighty male patients with first-episode depressive disorder were randomly selected. Forty male adolescent depressed patients with NSSI behaviors were set as the NSSI group, and forty male adolescent depressed patients without NSSI behaviors were set as the No-NSSI group. Their thyroid hormones and sex hormones were measured, and the severity of self-injury in the NSSI group was assessed using the Adolescent Self-Injury Questionnaire. The NSSI group was tested again after 6 weeks of sertraline treatment for biological indicators and assessed by the Self-Injury Questionnaire to compare the hormonal differences between the NSSI group and the No-NSSI group and compare the differences of each index before and after treatment in the NSSI group. Results T3/T4(p=0.001) and FT3(p=0.023), TSH levels(p<0.001) were lower in the NSSI group than in the No-NSSI group before treatment, and FT4(p=0.036) and T(p<0.001) levels were higher than in the No-NSSI group. T3/T4 levels were higher in the NSSI group after treatment (p<0.001). FT4(p<0.001) and T(p=0.001) levels and self-injury questionnaire scores(p<0.001) decreased after treatment in the NSSI group. In the NSSI group at baseline, FT4 levels were negatively correlated with self-injury questionnaire scores(r=-0.459, p=0.003) and testosterone levels were positively correlated with self-injury questionnaire scores(r=0.383, p =0.015), and in the NSSI group after treatment, FT4 difference was negatively correlated with self-injury questionnaire score reduction rate(r=-0.037, p=0.019), and testosterone difference was positively correlated with self-injury questionnaire score reduction rate(r=0.424, p=0.006). Logistic regression analysis showed that low TSH and high testosterone levels were independent risk factors for the development of non-suicidal self-harming behaviors in male adolescent depressed patients. Conclusion Changes in thyroid hormone and sex hormone levels may be associated with nonsuicidal self-injurious behavior in male adolescent depressed patients.